Venous In-stent Thrombosis Treated by Ultrasound Accelerated Catheter Directed Thrombolysis. Issue 4 (April 2015) - Strijkers, R.H.W.; de Wolf, M.A.F.; Arnoldussen, C.W.K.P.; Timbergen, M.J.M.; de Graaf, R.; Ten Cate-Hoek, A.J.; Wittens, C.H.A.
Abstract : Objective/Background: Stent placement in the venous system is an increasingly used treatment modality in chronic venous obstruction and as additional treatment after thrombolytic therapy in ilio-femoral deep vein thrombosis (DVT). Experience in treating in-stent thrombosis with ultrasound accelerated catheter directed thrombolysis (UACDT) is reported. Methods: A retrospective analysis of patients treated for venous stent occlusion, after percutaneous transluminal angioplasty (PTA) and stent placement for either chronic venous occlusive disease or persistent vein compression in patients with acute DVT was performed. Duration of occlusion and suspected clot age were assessed using patient complaints and typical findings on duplex ultrasonography (DUS). DUS and venography were used to assess patency and to determine the cause of re-occlusion. Acute treatment of occlusion was by UACDT. Additional procedures included PTA, stent placement, and creation of an arteriovenous (AV) fistula. Results: Eighteen patients (median age 43 years; 67% male), treated for occluded stent tracts with UACDT between January 2009 and July 2014, were identified. Indications for initial stenting were treatment of chronic venous obstructive disease (12 patients) and treatment of underlying obstruction after initial thrombolysis in acute DVT (six patients). Technical success was achieved in 11/18 (61%) patients. Primary patency in 8/11 patients was 73% at last follow up (median follow up 14 months [range 0–41 months]). Additional treatments after successful lysis were re-stenting (seven patients) and creation of an AV fistula (six patients). Conclusion: Treatment with UACDT of recently occluded stent tracts is feasible and effective. Recanalization of the stent tract can be achieved in most cases. Additional interventions were frequently used after successful UACDT treatment. Suboptimal stent positioning caused the majority of the stent occlusions.